(untitled) (Annals of Medical Research, 2021)
Aim: Certain NF1 patients have short stature due to unclear pathogenesis mechanisms. The aim of this study is to investigate endocrinology parameters which could affect height in NF1. Materials and Methods: Clinical data of 48 NF1 patients aged 19 months to 18 years were collected by reviewing medical records. Current physical examination findings including height, weight, and pubertal status were recorded. Serum samples were obtained from all subjects for follicle stimulating hormone (FSH), luteinizing hormone (LH), thyroid stimulating hormone (TSH), free T4 (FT4), free T3 insulin-like growth factor (IGF1), and insulin-like growth binding protein3 (IGFBP3) levels. Results: Of the 48 patients, 34 (70%) had height below 50 percentiles. Short stature, defined as height <-2 SD of mean for age and gender, was found in 25% of the patients. Pubertal children with short stature had significantly lower serum median IGF1 level than those with normal height. In the pre-pubertal group, serum median TSH level was significantly higher in those with short stature than those of normal height. Conclusion: Short stature in NF1 might be related to TSH in the pre-pubertal period and to IGF1 after puberty. Investigation of these hormonal pathways in correlation with height appears warranted in children with NF1.